STREAMLINING CLOUD APPLICATION WITH AI TECHNOLOGY - LAKSHMISRI SURYA (International Journal of Innovations in Engineering Research and Technology, 2018)
Artificial intelligence (AI) technology refers to imitating human intelligence in machines programmed to think like a human being and imitate their actions. Artificial intelligence is also associated with the human mind, including problem-solving. Artificial intelligence technology has turned to be a necessity in promoting the function of cloud applications. Cloud applications are adopted in a cloud environment instead of being hosted on a local machine or server. In the future, artificial intelligence (AI)is likely to effectively change cloud application performance and transform both marketing strategies, organization workflow, and customer behaviors. With artificial intelligence, organizations can streamline cloud computing applications necessary in organization servers and machines.